Mitochondria Dysfunction and Neuroinflammation in Neurodegeneration: Who Comes First? - Caterina Peggion; Tito Calì; Marisa Brini (MDPI AG, 2024)
Neurodegenerative diseases (NDs) encompass an assorted array of disorders such as Alzheimer's disease, Parkinson's disease, and amyotrophic lateral sclerosis, each characterised by distinct clinical manifestations and underlying pathological mechanisms. While some cases have a genetic basis, many NDs occur sporadically. Despite their differences, these diseases commonly feature chronic neuroinflammation as a hallmark. Consensus has recently been reached on the possibility that mitochondria dysfunction and protein aggregation can mutually contribute to the activation of neuroinflammatory response and thus to the onset and progression of these disorders. In the present review, we discuss the contribution of mitochondria dysfunction and neuroinflammation to the aetiology and progression of NDs, highlighting the possibility that new potential therapeutic targets can be identified to tackle neurodegenerative processes and alleviate the progression of these pathologies.